DIGITAL INTEGRATED MARKETING COMMUNICATIONS (DIMC) ACTIVITIES OF DIGITAL PRODUCTS FINANCIAL TECHNOLOGY (FINTECH) “ALAMI” - Baharudin Noveriyanto; Sa’diyah El Adawiyah (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Abstract. The development of information and communication technology has now had a major impact on the industrial world in Indonesia. Changes in the industrial model towards digital have a major influence on marketing activities carried out by companies so that they can win the competition in the midst of increasingly sharp business competition. The ability to adapt and innovate quickly and precisely by involving various digital communication media and marketing technology will have a positive influence on the company. ALAMI is a digital-based sharia financial product brand (financial technology), where the name ALAMI is taken from the prefix of the verse in the Al-Quran, namely